2018
DOI: 10.1364/ol.43.002400
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical susceptibility of two-dimensional WS2 measured by hyper Rayleigh scattering: erratum

Abstract: This erratum corrects errors in the expressions for ⟨β⟩ and fitted form of I and a consequent data point in Fig. 4 of a recent Letter [Opt. Lett.42, 5018 (2017)OPLEDP0146-959210.1364/OL.42.005018]. It also supplies data for the reference compound para-nitroaniline (pNA). The correction to ⟨β⟩ improves experimental agreement from 46% to within 21% of independent scissors-corrected density functional theory (DFT) calculations. Central findings from the original Letter remain intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…For Absolute measurements of χ (2) are then performed at 1064 nm from the linear increase in SH intensities versus TMD (and pNA) concentrations, as described in Ref. [22]. From the measured slopes in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For Absolute measurements of χ (2) are then performed at 1064 nm from the linear increase in SH intensities versus TMD (and pNA) concentrations, as described in Ref. [22]. From the measured slopes in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For spherical nanoparticles, T is calculated from the quasistatic approximation provided for a sphere, which allows us to estimate the inner field according to the refractive indices of the solvent and of the particles [36]. However, this approximation is no longer appropriate for a 2D nanosheet, and we here assume, because of the ultrathin monolayer thickness, that the incident fundamental field is not modified within the nanosheet, i.e., T = 1 [22]. Importantly, this assumption is the same as the one commonly used to describe a nonlinear polarization sheet deposited on top of a substrate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This value reported here for GO sheets is in the same order of magnitude than that reported for 2D WS2 monolayers under 1064 nm laser irradiation using paranitroaniline as the external reference. 30,31 However, the SHG signal in 2D WS2 monolayers may find a different origin as compared to the SHG signal in GO because WS2 monolayers lack inversion symmetry and have therefore a non-vanishing first hyperpolarizability. Further analysis through DFT calculations have indicated that this large first hyperpolarizability in WS2 monolayers is due to resonance enhancement as well as the presence of a large joint density of states.…”
Section: Second Harmonic Scattering From Mass Characterized 2d Graphementioning
confidence: 99%